Proceedings of the 2011 International Conference on Electrical Engineering and Informatics 2011
DOI: 10.1109/iceei.2011.6021634
|View full text |Cite
|
Sign up to set email alerts
|

Information extraction from scientific paper using rhetorical classifier

Abstract: Time constraints often lead a reader of scientific paper to read only the title and abstract of the paper, but reading these parts is often ineffective. This study aims to extract information automatically in order to help the readers get structured information from a scientific paper. The information extraction is done by rhetorical classification of each sentence in a scientific paper. Rhetoric information is the intention to be conveyed to the reader by the author of the paper. This research used corpusbase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Tokenization is the process of parsing a sentence or paragraph into units of words, referred to as tokens [3,13]. Each token will be a feature in the classification process [2]. This feature has a positive effect on accuracy.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Tokenization is the process of parsing a sentence or paragraph into units of words, referred to as tokens [3,13]. Each token will be a feature in the classification process [2]. This feature has a positive effect on accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…These features consider the meaning of a word, such as its semantic features, and relations between words and sentences. An easy way to determine the relationship between sentences is classifying them based on rhetorical categories [2,16]. Teufel, et al [17] introduced 15 rhetorical categories in scientific papers, as shown in Table 1.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A rhetorical category is assigned for each sentence of the 75 papers in the collection. The result is an annotated corpus of 10877 rhetorically labeled sentences [35]. This corpus is then randomly split into a training set and a test set.…”
Section: Evaluation Of Rdp Extraction Modulementioning
confidence: 99%